Clinical Significance of Salivary Matrix Metalloproteinase-9 in Oral Precancerous Conditions and Oral Cancer - Vajaria, Bhairavi N; Patel, Kinjal R; Begum, Rasheedunnisa; Shah, Franky D; Patel, Jayendra B; Joshi, Geeta M; Patel, Prabhudas S (Cancers Review, 2014)
Background: Oral cancer is a one of the major health burden worldwide and also in India. The most strenuous problem in oral cancer is metastasis, where use of newer non-invasive biomarkers for early detection of metastatic tumors would be greatly helpful. Aim: The aim was to evaluate salivary matrix metalloproteinase-9 in patients with oral precancerous conditions (OPC) and oral cancer to assess its utility in monitoring oral cancer progression. Subjects and Methods: Total 250 subjects including 100 controls, 50 patients with OPC and 100 oral cancer patients were enrolled for the study. Gelatin zymography was performed for the evaluation of matrix metalloproteinase (MMP)-9 and truncated 42 kDa MMP. Statistical Analysis: Statistical analysis like Student’s independent‘t’ test, Receiver’s Operating Characteristic (ROC) curve, correlation and multivariate analysis were performed to analyze the results. Results: A truncated form of MMP i.e. 42 kDa was observed to have gelatinolytic activity. An increasing trend of salivary pro MMP-9, active MMP-9, MMP-9 activation ratio and truncated 42 kDa MMP was observed from controls to patients with OPC to oral cancer patients. ROC curve analysis revealed that all forms of MMPs could significantly discriminate controls and oral cancer patients; moreover, pro MMP-9 and active MMP-9 significantly distinguished patients with OPC and oral cancer patients. All the levels were found to be higher in patients with advanced disease and with metastasis as compared to patients with early disease and without metastasis, respectively. Conclusion: Elevated levels of salivary MMP-9 and truncated 42 kDa MMP in patients with OPC and oral cancer may be important for assessing early changes occurring during neoplastic transformation of oral cancer.